Review of Pharmaceutical Applications of N-Methyl-2-Pyrrolidone - Abolghasem Jouyban; Mohammad Amin Abolghasemi Fakhree; Ali Shayanfar (Frontiers Media S.A., 2010)
N-Methyl-2-pyrrolidone (NMP) or Pharmasolve is very strong solubilizing agent and it has important applications in different fields of industry. This review presents NMP physicochemical characteristics, application especially in pharmaceutical sciences, pharmacokinetic and toxicity. Characteristics of NMP such as physicochemical properties, solubilization efficacy, toxicity and adverse effects were compared with other common solvents used in the pharmaceutical industries. This review reveals that NMP is an acceptable pharmaceutical solvent and its efficacy, toxicity, and side effects are comparable with other common solvent.